A Comprehensive Family of Biunivalent Functions Defined by k-Fibonacci Numbers. (31st October 2021) - Frasin, Basem Aref; Swamy, Sondekola Rudra; Aldawish, Ibtisam
Abstract : By using k -Fibonacci numbers, we present a comprehensive family of regular and biunivalent functions of the type g z = z + ∑ j = 2 ∞   d j z j in the open unit disc D . We estimate the upper bounds on initial coefficients and also the functional of Fekete-Szegö for functions in this family. We also discuss few interesting observations and provide relevant connections of the result investigated.